SAT0148 Similar Improvements in Quality of Sleep, Satisfaction with Medication and Sexual Impairment Among Rheumatoid Arthritis Patients Upon Initiation of Adalimumab in Combination with Two Doses of Methotrexate. (9th June 2015) - Kaeley, G.; Nishio, M.J.; MacCarter, D.; Griffith, J.; Garg, V.; Kupper, H.; Kalabic, J.
Abstract : Background: Methotrexate (MTX) is used as monotherapy or in combination with other DMARDs in the treatment of patients (pts) with rheumatoid arthritis (RA). Objectives: To evaluate the effects of low and high MTX doses in combination with initiation of ADA on patient-reported outcomes (PROs) in MTX-inadequate responders (MTX-IR) with moderate-to-severe RA. Methods: MUSICA (NCT01185288 ) was a randomized, double-blind, controlled trial evaluating the efficacy of two different dosages of MTX, 7.5 or 20 mg/week (wk) in combination with ADA (40 mg every other wk) for 24 wks in MTX-IR RA pts. Pts entering the study had been receiving ≥15 mg/wk MTX for at least 12 wks. At each study visit, from baseline (BL) to wk 24, the following PROs were recorded: quality of sleep, using the Medical Outcomes Sleep (MOS) Index II; Satisfaction with treatment medication, using the Treatment Satisfaction Questionnaire for Medication (TSQM); and sexual impairment due to RA, using a single question of how much did your RA affect sexual functioning over the past 7 days. Last observation carried forward (LOCF) was used to account for missing values. Results: 154 pts were enrolled in the 7.5 mg/wk MTX+ADA arm, and 155 pts in the 20 mg/wk MTX+ADA arm. Both arms were similar for BL demographics (mean age 54.8, 25.2% male), disease characteristics (mean disease duration 5.3 years; mean DAS28(CRP) of 5.8). BL values for MOS, TSQM and sexual impairment were similar. At wk 24 after treatment, improvements were observed in all subdomains of the MOS Sleep Index and the TSQM, and Sexual Impairment due to RA (Table ). Except for the MOS Sleep Index-Awakened Short of Breath/headache domain, TQSM-Side effects and TQSM-Convenience, the differences from BL were statistically significant. At wk 24, the difference between the scores for the two treatment groups was not statistically significant for any of the subdomains in the MOS Sleep Index or the subdomains in the TSQM, except for Convenience (p=0.023), which was lower for the 20 mg/wk MTX dosage group. At wk 24 after treatment, the difference between the scores between the two treatment groups was not statistically significant for Sexual Impairment. Conclusions: Similar to observations in pts with early RA (1), the addition of ADA to MTX in pts with moderate-severe disease and insufficient MTX response, led to improvements in quality of sleep, and satisfaction with treatment medication after 24 wks. Improvements in sexual impairment were also observed. Improvements in all three PROs were observed regardless of the concomitant MTX dosage. References: Burmester et al; ARD 2014; 0:1-8 Acknowledgements: AbbVie sponsored the study (NCT01185288 ), contributed to its design, participated in the collection, analysis, and interpretation of the data, and in the writing, reviewing, and approval of the final version. Statistical support was provided by Peigang Li, PhD, and Shufang Liu, PhD; medical writing support was provided by Naina Barretto, PhD, all of AbbVie. Disclosure of Interest: G. Kaeley Consultant for: AbbVie, M. Nishio Speakers bureau: AbbVie, D. MacCarter Consultant for: AbbVie, Speakers bureau: AbbVie, J. Griffith Employee of: AbbVie, V. Garg Employee of: AbbVie, H. Kupper Employee of: AbbVie, J. Kalabic Employee of: AbbVie